The Effect Of Giving Pregnant Women Milk And Supplementary Food on Weight Gain in Pregnant Women in Deli Tua District - Tedty Rohaya Tinambunan; Roikestina Silaban; Sulastri Br Ginting (BEST Journal (Biology Education, Sains and Technology), 2023)
This study aims to see the effect of giving special milk for pregnant women and additional food on weight gain in pregnant women. The main target is weight gain for pregnant women in the Deli Tua sub-district. This study used a quasi-experimental method in which the research design used was one group test with pre-test and post-test designs without a control group. This study used a sample of 15 pregnant women in the 1st trimester who were indicated to be underweight. The results of the study showed that there was a significant difference in the weight of pregnant women before and after being given milk and supplementary food to the experimental group (at the level of p0.05). The conclusion obtained is that the provision of milk and additional food has an effect on weight gain in pregnant women. This program can be applied in further practice for further research and discussion of reference for further midwifery activities.